PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS VIIIJ PADA MATERI STATISTIKA MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK - Azzahro, Elok Fatima; Harijanto, Slamet; Susanah, Susanah (Universitas Tribhuwana Tunggadewi, 2023)
This study aims to improve the learning outcomes of students in class VIII J SMP Negeri 1 Pamekasan. This study uses PTK research on statistical material through the application of a project-based learning model through two learning cycles. This study used 2 cycles where each cycle consisted of three meetings in each learning implementation. The results of the study in cycle I the percentage of completeness of student learning outcomes was 51.9% and increased in cycle II by 66.7% with a percentage increase of 14.8%. So it can be concluded that learning by applying a project-based learning model can improve the learning outcomes of grade VIII J students of SMP Negeri 1 Pamekasan on statistical material. This shows that project-based learning models can improve student statistical learning outcomes.